Avian migration and the distribution of malaria parasites in New World passerine birds. (18th December 2016) - Ricklefs, Robert E.; Medeiros, Matthew; Ellis, Vincenzo A.; Svensson‐Coelho, Maria; Blake, John G.; Loiselle, Bette A.; Soares, Leticia; Fecchio, Alan; Outlaw, Diana; Marra, Peter P.; Latta, Steven C.; Valkiūnas, Gediminas; et al.
Abstract: Aim: Migrating birds transport their parasites, often over long distances, but little is known about the transfer of these parasites to resident hosts in either the wintering or breeding ranges of the migratory host populations. We investigated the haemosporidian parasite faunas of migratory and resident birds to determine connections among distant parasite faunas, plausibly brought about by migratory host populations. Location: Samples were obtained, primarily during or shortly after the local breeding season, throughout the Americas, from the United States through the Caribbean Basin and into northern South America. Methods: Infections were identified by PCR and sequencing of parasite DNA in avian blood samples. The analyses were based on c . 4700 infections representing 79 parasite lineages of Plasmodium and Haemoproteus spp. Geographical connections of lineages between regions in the Americas were compared to those in the Euro‐African migration system, where migration distances are longer for many host species and the migrant and resident avifaunas in the wintering areas are phylogenetically more divergent. Results: Haemosporidian lineages exhibited considerable variation in distribution in the Americas, and patterns of distribution differ markedly between the Americas and the Euro‐African migration system. In particular, few lineages were recovered from resident species in both temperate and tropical latitudes, particularly in the Euro‐African system, in which a large proportion of lineages were restricted to migrants. Parasite lineages in the Euro‐African system exhibited considerable phylogenetic conservatism in their distributions, that is, a tendency of related lineages to exhibit similar geographical distributions. In contrast, clades of parasites in the Americas displayed more geographical diversity, with four of 12 clades exhibiting all four of the distribution types representing the combinations of resident and migrant host species in both temperate and tropical latitudes. Main conclusions: Long‐distance migrants connect communities of avian haemosporidian parasites in breeding and wintering areas with disparate avifaunas and different vector communities. The degree of parasite lineage sharing between migrants and residents in breeding and wintering areas appears to reflect, to a large degree, the taxonomic similarity of migrants to the resident species in both areas.